The effect of gender role orientation on student nurses' caring behaviour and critical thinking. (January 2019) - Liu, Nai-Yu; Hsu, Wen-Yi; Hung, Chao-An; Wu, Pei-Ling; Pai, Hsiang-Chu
Abstract: Aim: We explored the impact of gender role orientation (masculinity and femininity) on student nurses' caring behaviour and critical thinking. Background: Caring and critical thinking are at the core of professional nursing education. Previous studies revealed inconsistent findings regarding the impact of gender roles on caring behaviour and critical thinking. Design and Methods: We employed a quantitative correlational study. Nursing students ( N = 449; female = 310, male = 139) who had at least had one month of clinical practice experience were recruited from four universities in Taiwan. Students' ages ranged from 19 to 29 years (Mean age = 21.24 years, SD = 1.28). Data were collected from August 2016 to July 2017, using three questionnaires: Taiwan Critical Thinking Disposition Inventory (CTDI), Caring Assessment Report Evaluation Q-sort Scale (CARE-Q), and Bem Sex Role Inventory (BSRI). Partial least squares structural equation modelling and generalized linear models were conducted to test the research model and hypotheses. Results: Findings indicated that students who reported higher caring and masculinity presented greater critical thinking (ß = .37 and ß = 0.24, respectively; p s < .001). Students' gender, age, femininity, or clinical practice experience, however, were not significantly associated with critical thinking ( ß = -0.01, ß = 0.09, ß = .10, and ß = 0.01, respectively; p s > .05). In addition, students who reported higher masculinity and femininity presented greater caring behaviour ( ß = .22 and ß = 0.38, respectively; p s < .001). Students' gender, age or clinical practice experience were not significantly associated with caring behaviour ( ß = .04, ß = .03, and ß = -0.05, respectively; ps > 0.05). The findings confirmed a direct influence of caring and masculinity on critical thinking. Masculinity indirectly affected critical thinking via caring behaviour. Caring and masculinity accounted for 34.4% of the variance in critical thinking, and masculinity and femininity accounted for 29.1% of the variance in caring behaviour. Conclusion: Our study confirms the effect of age, gender role, and caring behaviour on critical thinking. We recommend that the cultivation of nursing care behaviour focus on students' gender role orientation. In addition, clinical nurse educators, when working with male students on patient caring, should consider their gender role orientation and support male nursing students' ways of presenting caring behaviours.